On a production function of European countries: An empirical study - Jiří Mazurek (Comparative Economic Research. Central and Eastern Europe, 2018)
The aim of this paper is to examine the goodness-of-fit of several aggregated production functions including the Cobb-Douglas function, the Mankiw, Romer and Weil model, or Mincer's specification for a set of 30 European countries during the period 2006-2015. The dependent variable was economic output measured in real GDP, while the set of independent variables included labour, physical capital, human capital, labour productivity or technology level. The main finding of the paper is that all the above-mentioned aggregate production functions fitted the data exceptionally well, with the adjusted coefficients of determination above 0.95. Also, it was found that the inclusion of other macroeconomic variables, such as labour productivity, human capital or technology level to the two-factor Cobb-Douglas function did not result in a significantly better goodness-of-fit.
Keywords: E01; E23; R12; 330; cross-sectional study; production function; European countries